Housing markets and the global financial crisis the uneven impact on households - Forrest, Ray; Yip, Ngai-ming (Edward Elgar, 2011)
Housing markets were at the centre of the recent global financial turmoil. In this study, a multidisciplinary group of leading housing analysts from the USA, Europe, Asia and Australasia explore the impact of the crisis within and between countries.